Optimisation of enzymatic protein hydrolysis of mud crab (Scylla sp.) to obtain maximum antioxidant activity using response surface methodology - Zaliha Harun,; Amiza Mat Amin,; Norizah Mhd Sarbon,; Mohamad Khairi Mohd Zainol,; Kazi Nazira Sharmin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study reported optimisation of enzymatic hydrolysis of mud crab meat using Protamex® to obtain maximum antioxidant activity using Response Surface Methodology (RSM). Prior to optimisation, screening of commercial food grade proteinases was carried out using Alcalase®, Protamex®, Neutrase® and papain. Protamex® was observed to give the highest DPPH scavenging activity. The enzymatic hydrolysis conditions used in the optimisation study were temperature (45-65ºC), pH (5.5-7.5), hydrolysis time (1-4 hours) and enzyme to substrate (E/S) ratio (1-3% Protamex®). A face-centered Central Composite Design (CCD) was employed. It was found that the relationship between hydrolysis conditions and DPPH scavenging activity could be explained by a quadratic model. Optimum condition was found to be at 54ºC, pH 5.5, 1% Protamex® and 1 hour of hydrolysis time. Validation experiment shows that the experimental DPPH scavenging activity (82.39 ± 0.16%) was close to the predicted value (82.64%). The hydrolysate prepared at optimum condition contained 5.52% moisture, 74.81% crude protein, 13.13% ash, 6.26% carbohydrate and 0.28% crude fat with IC50 for DPPH scavenging activity of 3.48 ± 0.05 mg/mL. This study shows that RSM can be used to explain the relationship between enzymatic hydrolysis conditions of mud crab meat and its antioxidant activity.